Engineering thermal stability and solvent tolerance of the soluble quinoprotein PedE from Pseudomonas putida KT2440 with a heterologous whole‐cell screening approach. Issue 2 (14th December 2017) - Wehrmann, Matthias; Klebensberger, Janosch
Summary: Due to their ability for direct electron transfer to electrodes, the utilization of rare earth metals as cofactor, and their periplasmic localization, pyrroloquinoline quinone‐dependent alcohol dehydrogenases (PQQ‐ADHs) represent an interesting class of biocatalysts for various biotechnological applications. For most biocatalysts protein stability is crucial, either to increase the performance of the protein under a given process condition or to maximize robustness of the protein towards mutational manipulations, which are often needed to enhance or introduce a functionality of interest. In this study, we describe a whole‐cell screening assay, suitable for probing PQQ‐ADH activities in Escherichia coli BL21(DE3) cells, and use this assay to screen smart mutant libraries for increased thermal stability of the PQQ‐ADH PedE (PP_2674) from Pseudomonas putida KT2440. Upon three consecutive rounds of screening, we identified three different amino acid positions, which significantly improve enzyme stability. The subsequent combination of the beneficial mutations finally results in the triple mutant R91D/E408P/N410K, which not only exhibits a 7°C increase in thermal stability but also a twofold increase in residual activity upon incubation with up to 50% dimethyl sulfoxide (DMSO), while showing no significant difference in enzymatic efficiency ( k cat / K M ). Abstract : Pyrroloquinoline quinone (PQQ) dependent enzymes represent an interesting class of alcohol dehydrogenases (ADHs) due to their periplasmic localization, their ability to be directly coupled to electrodes, and because they can utilize lanthanides as metal cofactors. This study shows that thermal stability and solvent tolerance of the soluble PQQ dependent ADH PedE from Pseudomonas putida KT2440 is dependent on cofactor binding and can be strongly increased by rigidifying flexible amino acid residues near the active site.